Identifying School Principal Candidates’ Perception on Teacher’s Appointment as School Principal - Nunuk Hariyati; Tarma Tarma; Dian Fajarwati; Aditya Chandra Setiawan (Universitas Pendidikan Ganesha, 2021)
In order to establish a successful school, prospective school principals' perceptions are crucial. Perception has an effect on school quality because it impacts reaction and decision-making. The aim of this study was to understand prospective school principals' perceptions of the Ministry of Education and Culture Regulation Number 6 of 2018 concerning the Appointment of Teachers as School Principals, which was conducted using a quantitative approach through a survey of 77 prospective school principals from Central and East Java Provinces. The findings revealed that: the age of the prospective school principal does not have a significant effect on policy perceptions; the length of work as a prospective school principal teacher has no significant effect on policy perceptions; there is a significant difference between the principal candidates for primary school, junior high school and senior high school/vocational high school in perceiving policies; there is no significant difference between male and female principal candidates in their perception of the policy; there is no significant difference between prospective school principals based on tank (from III b to IV b) in perceiving policies; there is a significant difference between prospective school principals with bachelor's and master's degrees in perceiving policies; there is no significant difference between prospective school principals who have not and have read Ministry of Education and Culture Regulation No. 6 of 2018 in perceiving the policy; and that there is no significant difference between prospective school principals who have not and have specifically reviewed Ministry of Education and Culture Regulation No. 6 of 2018 in perceiving the policy.